2015
DOI: 10.1152/ajprenal.00202.2014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pelvic allodynia is mediated by CCL2 through mast cells in an experimental autoimmune cystitis model

Abstract: The cause of chronic pelvic pain in interstitial cystitis/painful bladder syndrome (IC/PBS) remains unclear; autoimmunity is a possible etiology. We have recently shown that injection of a single immunogenic peptide of uroplakin 3A (UPK3A 65-84) induces experimental autoimmune cystitis (EAC) in female BALB/cJ mice that is unique among experimental models in accurately reflecting both the urinary symptoms and pelvic pain of IC/PBS. The aim of this project was to identify the roles of mast cells and mast cell ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 58 publications
1
38
0
1
Order By: Relevance
“…Clinical trials in IC/BPS using mast cell inhibitors have been conducted and demonstrated to be promising [46]. In line with human studies, animal studies have demonstrated that mast cells are responsible for bladder inflammation and pain in diverse models [710]. However, despite these studies, the role of mast cells in cystitis-associated LUTD has not been identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials in IC/BPS using mast cell inhibitors have been conducted and demonstrated to be promising [46]. In line with human studies, animal studies have demonstrated that mast cells are responsible for bladder inflammation and pain in diverse models [710]. However, despite these studies, the role of mast cells in cystitis-associated LUTD has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models with bladder autoimmune inflammation have been actively used in IC/BPS research for over two decades [10,1924]. Experimental autoimmune cystitis (EAC) can be induced through immunization with bladder tissue components in rodents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when BMMCs were pretreated with supernatant from IBS-D mucosal biopsy samples6 for 60 min, PAR4-AP significantly decreased Agrin, CINC-1, CINC-2α, CINC-3, MCP-1 and TIMP-1 expression and increased Fas Ligand, Fractalkine, granulocyte macrophage colony-stimulating factor, IFN-γ, Leptin and IL-13 protein levels in supernatant-pretreated BMMCs (figure 2C). MCP-1 and MCs infiltration were previously identified in chronic visceral allodynia,7 and this can potentially be prevented by PAR4 agonism. However, these experiments were performed on cultured MCs that may have had a different phenotype compared with MCs residing in their natural microenvironment; these results may also be rat specific and may not reflect human MC physiology.…”
mentioning
confidence: 91%
“…Lokal olarak prostatta meydana gelen patoloji doku düzeyinde hassasiyet ve basınç oluşturmaktadır. Burada bahsedilen sitokinler ve kemokinler hücre sinyal molekülleridir ve gerek proinflamatuar, gerek inflamatuar gerekse de onarım sürecinde yer alan çok sayıda alt başlıkta incelenmektedir (45)(46)(47)(48)(49)(50). Bu hücre sinyalleri aracılığı ile lökositler artmakta ve ekstraprostatik sekresyonda (EPS) saptanmaktadır.…”
unclassified